Xuefu Zhuyu decoction ameliorates obesity, hepatic steatosis, neuroinflammation, amyloid deposition and cognition impairment in metabolically stressed APPswe/PS1dE9 mice. (14th September 2017) - Yeh, Chih-Wen; Liu, Hui-Kang; Lin, Lie-Chwen; Liou, Kou-Tong; Huang, Yung-Cheng; Lin, Chien-Hung; Tzeng, Tsai-Teng; Shie, Feng-Shiun; Tsay, Huey-Jen; Shiao, Young-Ji
Abstract: Ethnopharmacological relevance: Metabolic syndrome and vascular dysfunction was suggested to be the risk factors for Alzheimer's disease (AD). Xuefu Zhuyu decoction (XZD) is a traditional Chinese medicine used to treat metabolic syndrome and cardiac-cerebral vascular disease. The effects of XZD on ameliorating metabolic syndrome, amyloid-related pathologies and cognitive impairment in an animal model of AD with metabolic stress was investigated. Materials and method: The animal model of AD with metabolic stress was created by administrating high-fat diet and a low-dose injection of streptozotocin prior to the appearance of senile plaques in APP/PS1 transgenic mice. The diabesity-associated metabolic changes and AD-related pathological alterations were examined. Results: We found that XZD reduced body weight, insulin and leptin level, HOMA-IR, hepatic triglyceride, serum Aβ42 in the metabolic stressed AD animal. XZD also ameliorated oral glucose tolerant, Aβ deposition, astrocyte and microglia activation in the vicinity of plaques, and nesting behavior in the metabolic stressed AD animal. Conclusion: The results of this study suggest that XZD is able to reduce the peripheral metabolic stress-mediated vascular hypoperfusion, neuroinflammation and AD-related pathology in APP/PS1 mice. Graphical abstract: